Gel electrolyte, lithium ion battery and preparation method thereof
By employing a three-dimensional network structure of PVFH-PVCA matrix and initiator crosslinking technology in lithium-ion batteries, the problem of structural degradation of gel electrolytes at high temperatures is solved, thereby improving the stability of the electrolyte, the safety of the battery, and its cycle life.
Patent Information
- Application Number
- CN202511039066.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-11-25
AI Technical Summary
During long-term use, especially under high-temperature conditions, gel electrolytes may undergo structural degradation, leading to a decline in their physical properties and electrochemical performance, which affects the stability and reliability of lithium-ion batteries.
Poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate (PVFH-PVCA) is used as the main polymer matrix, and cross-linking is achieved by generating free radicals through an initiator to form a three-dimensional network structure. Combined with the polymer sub-matrix, lithium salt, organic solvent, solid electrolyte and film-forming aid, a stable gel electrolyte is formed.
It enhances the mechanical strength and toughness of the electrolyte, provides a continuous ion transport path, improves the stability and high ionic conductivity of the electrolyte, prevents decomposition under high pressure conditions, and improves the safety and cycle stability of lithium-ion batteries.
Smart Images

Figure CN121011707A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium battery, in particular to a gel electrolyte, a lithium ion battery and a preparation method thereof. BACKGROUND
[0002] In the technical field of lithium ion battery, especially in lithium ion battery, gel electrolyte as a kind of electrolyte form between liquid and solid, has been widely concerned because of its advantages of both. Conventional liquid electrolyte has the disadvantages of leakage risk, flammability and poor temperature adaptability, while solid electrolyte can overcome these problems, but the poor interface contact between the electrode often leads to high internal resistance and low ionic conductivity. In contrast, gel electrolyte can effectively improve these problems by fixing an appropriate amount of liquid electrolyte in the polymer matrix, while maintaining high ionic conductivity and good interface compatibility.
[0003] However, during long-term use, especially under high temperature conditions, the gel electrolyte may have structural degradation, leading to a decline in its physical properties and electrochemical performance, and affecting the stability and reliability of the lithium ion battery. SUMMARY
[0004] The main purpose of the present application is to provide a gel electrolyte, a lithium ion battery and a preparation method thereof, which aims to solve the technical problem of poor stability of gel electrolyte.
[0005] To achieve the above-mentioned purpose, the present application provides a gel electrolyte, comprising: a polymer main matrix, an initiator, a lithium salt, an organic solvent, a solid electrolyte and a film-forming aid, wherein the polymer main matrix comprises: poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate.
[0006] In an embodiment, the gel electrolyte comprises, in mass percentage: 0.1-1% of the polymer main matrix, 0.1-1% of the initiator, 10-20% of the lithium salt, 20-65% of the organic solvent, 0.5-25% of the film-forming aid and 0.1-1% of the solid electrolyte.
[0007] In an embodiment, the gel electrolyte further comprises: a polymer auxiliary matrix, the polymer auxiliary matrix comprising: polyhexafluoropropylene and / or poly(vinylidene fluoride-hexafluoropropylene).
[0008] In an embodiment, the initiator comprises at least one of di(2-ethylhexyl)dicarbonate, benzoyl peroxide and potassium persulfate.
[0009] In an embodiment, the lithium salt comprises at least one of LiPF6, LiFSI, LiTFSI, LiBOB, LiDFOB and LiPO2F2.
[0010] In an embodiment, the organic solvent comprises at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, methyl ethyl carbonate, dimethylether, tetrahydrofuran, methyl acetate, ethyl acetate, methyl propionate, and diethyl carbonate.
[0011] In an embodiment, the solid-state electrolyte comprises at least one of LLTO, LATP, LLZO, Li2S-P2S5, Li 10 GeP2S 12 , Li3YCl6, and Li3YBr6.
[0012] In an embodiment, the film forming aid comprises at least one of vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, propylene sulfite, ethylene sulfate, trimethylsilyl borate, trimethylsiloxy propyl sulfonate, and cyclohexylbenzene.
[0013] Embodiments of the present application also provide a method for preparing a lithium ion battery, the method comprising the following steps:
[0014] providing an un-liquid injected battery and a gel electrolyte, wherein the gel electrolyte is as described above;
[0015] injecting the gel electrolyte into the un-liquid injected battery, and standing for 16-48 hours to obtain a pre-charged battery;
[0016] pre-charging and heat-pressing the pre-charged battery to obtain a lithium ion battery.
[0017] Embodiments of the present application also provide a lithium ion battery, which comprises a gel electrolyte as described above, or is prepared by a method for preparing a lithium ion battery as described above.
[0018] One or more technical solutions proposed in this application have at least the following technical effects: A gel electrolyte is provided, comprising: a polymer matrix, an initiator, a lithium salt, an organic solvent, a solid electrolyte, and a film-forming aid, wherein the polymer matrix comprises: poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate. In the embodiments of this application, poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate (PVFH-PVCA) is used as the polymer matrix, and cross-linking is achieved by generating free radicals through an initiator, thereby forming a three-dimensional network structure. This three-dimensional network structure restricts the mobility of the polymer chains, enhances the mechanical strength and toughness of the electrolyte, making it more resistant to external pressure and internal stress, reducing microcracks and delamination that may occur during battery cycling, and improving stability; at the same time, it also provides a continuous path for ion transport, effectively maintaining the high ionic conductivity of the electrolyte. Furthermore, PVFH-PVCA itself has good chemical inertness, and the presence of fluorine in particular endows the material with excellent antioxidant and corrosion resistance. Therefore, these properties are further enhanced after crosslinking, which helps to prevent the decomposition of the electrolyte under high pressure conditions and further improves the stability of the gel electrolyte. Attached Figure Description
[0019] Figure 1 This is a schematic flowchart of the gel electrolyte preparation method involved in the embodiments of this application.
[0020] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0022] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the gel electrolyte, lithium-ion battery, and preparation method thereof. However, unnecessary details may be omitted. For example, detailed descriptions of well-known facts and repetitive descriptions of essentially the same structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0023] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0026] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0027] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0028] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0029] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the technical solution of this application is further described below in conjunction with the accompanying drawings and embodiments. However, this application is not limited to the listed embodiments, but should also include any other well-known modifications within the scope of the claims made in this application.
[0030] The term "an embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of this application. The phrase "in one embodiment" appearing in different places throughout this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0031] To better understand the technical solution of this application, a detailed description will be provided below in conjunction with the accompanying drawings and specific implementation methods.
[0032] In conventional technologies, gel electrolytes may undergo structural degradation during long-term use, leading to a decline in their physical properties and electrochemical performance, thereby affecting the stability and reliability of lithium-ion batteries.
[0033] In this embodiment, poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate (PVFH-PVCA) is used as the main polymer matrix and combined with a secondary polymer matrix. Crosslinking is achieved by generating free radicals through an initiator, thereby forming a three-dimensional network structure. This three-dimensional network structure restricts the mobility of polymer chains, enhances the mechanical strength and toughness of the electrolyte, making it more resistant to external pressure and internal stress, reducing microcracks and delamination that may occur during battery cycling, and improving stability. At the same time, it also provides a continuous path for ion transport, effectively maintaining the high ionic conductivity of the electrolyte. Furthermore, PVFH-PVCA itself has good chemical inertness, especially the presence of fluorine, which endows the material with excellent antioxidant and corrosion resistance. Therefore, these properties are further enhanced after crosslinking, which helps prevent the decomposition of the electrolyte under high pressure conditions and further improves the stability of the gel electrolyte.
[0034] The first aspect of this application provides a gel electrolyte, which includes: a polymer matrix, an initiator, a lithium salt, an organic solvent, a solid electrolyte, and a film-forming aid, wherein the polymer matrix includes: poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate.
[0035] Optionally, the presence of poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate (PVFH-PVCA) provides excellent ionic conductivity due to the presence of polyacrylonitrile (PAN) and ethylene carbonate (EC), effectively dissociating lithium salts and providing a rapid ion transport pathway. PVDF-HFP serves as the basic mechanical support, and combined with PVCA, enhances the overall structural toughness. Through potential cross-linking initiated by maleic anhydride, the entire system becomes more robust and durable. Furthermore, each component in PVFH-PVCA has a relatively high thermal decomposition temperature; therefore, gel electrolytes prepared using PVFH-PVCA as the polymer matrix maintain good stability at high temperatures and are less prone to volatilization or decomposition.
[0036] In one feasible embodiment, the gel electrolyte further includes a polymer sub-matrix, which includes polyacrylonitrile and / or polyvinylidene fluoride-hexafluoropropylene.
[0037] Optionally, by selecting polyacrylonitrile (PVCA) and / or polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) with good compatibility with PVFH-PVCA as polymer sub-matrixes, the interfacial interactions between them can promote intermolecular diffusion, thereby forming a more compact network structure and improving the overall performance of the material.
[0038] In one feasible embodiment, the initiator includes at least one of di(2-ethylhexyl) dicarbonate, benzoyl peroxide, and potassium persulfate.
[0039] Optionally, by selecting at least one of di(2-ethylhexyl) dicarbonate (EHP), benzoyl peroxide (BPO), and potassium persulfate (KPS) as an initiator, it decomposes under certain conditions to generate free radicals, which attack unsaturated bonds or active sites (such as double bonds, amide bonds, etc.) on the polymer matrix and polymer sub-matrix chains, thereby initiating the reaction and forming new chemical bonds (such as ester bonds or amide bonds). These newly formed bonds connect different polymer chains and gradually construct a three-dimensional network structure.
[0040] Optionally, EHP can initiate moderate crosslinking of PVFH-PVCA, enhancing its mechanical strength and electrochemical stability. As an organic peroxide initiator, EHP undergoes homolytic cleavage under heating conditions, decomposing to generate highly reactive alkoxy radicals. These radicals attack PVFH-PVCA, whose PVCA segments contain active groups (such as the cyano group of acrylonitrile, the anhydride group of maleic anhydride, and the ester group of ethylene carbonate), making them susceptible to free radical attack. The generated radicals preferentially attack unsaturated or weak bond sites (such as anhydride groups) in PVCA, abstracting hydrogen atoms to form polymer radicals, initiating a chain reaction. If unstable CH bonds (such as vinylidene fluoride units) exist in the PVFH segments, they may also participate in the reaction. EHP undergoes homolytic cracking upon heating to generate ethylhexyl oxygen radicals and carboxyl radicals. The carboxyl radicals rapidly decarboxylate to form alkyl radicals. This reaction provides an initial radical source for crosslinking and an initial active species for polymerization. The radicals can attack the double bonds of monomers (such as ethylene, vinyl chloride, and acrylates) to initiate chain growth reactions, which form long polymer chains.
[0041] Optionally, EHP undergoes homolytic cleavage upon heating to generate ethylhexyl oxygen radicals and carboxyl radicals. The latter rapidly decarboxylates to form alkyl radicals. This reaction provides an initial radical source for crosslinking, initiating the activation of the PAN chain in PVFH-PVCA. Specifically, the alkoxy radicals from EHP decomposition preferentially attack the cyano groups in the PAN molecular chain. The strong electronegativity of the cyano group makes it a radical trapping site, forming an imine radical intermediate. The PAN cyano group may undergo intramolecular cyclization, forming a ladder structure rather than crosslinking. When PVDF-HFP is added as a polymer sub-matrix, it also reacts with EHP, resulting in crosslinking through synergistic and combined effects.
[0042] Optionally, BPO decomposes upon heating to generate highly reactive benzoyloxy radicals and benzyl radicals. The benzyl radicals further decarboxylate to generate phenyl radicals. These radicals act as initiators, abstracting active hydrogen atoms from the polymer chain. Specifically, the radicals abstract hydrogen atoms from -CH2- or -CF2- to generate alkyl radicals. The α-H atom of the anhydride ring is easily attacked to form a radical, or the carboxyl H atom formed after ring opening participates in the reaction, while the α-H atom of the cyano group is abstracted to generate methylene radicals. Finally, the generated polymer radicals combine to form C-C crosslinks, constructing a three-dimensional network structure.
[0043] Optionally, KPS decomposes upon heating to produce sulfate radicals and potassium ions, which further hydrolyze to generate hydroxyl radicals. These highly oxidizing radicals attack the active hydrogen sites on the polymer chain. Specifically, the radicals abstract the α-H adjacent to the cyano group to generate carbon-centered radicals, while the α-H of the anhydride ring or the H of the open-ring carboxyl group is abstracted. The strong electron-withdrawing effect of the fluorine atom makes it easier to abstract the H on the adjacent -CH2- or -CF2-. Finally, the polymer radicals generated combine with each other to form CC cross-linking bonds, constructing a three-dimensional network structure.
[0044] In one feasible embodiment, the lithium salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBOB, LiDFOB and LiPO2F2.
[0045] Alternatively, lithium salts serve as an ion source in the electrolyte, providing lithium ions for transport during battery charging and discharging. Lithium salts can also form a protective solid electrolyte interface (SEI) on the electrode surface, which helps improve battery safety and cycle life.
[0046] In one feasible embodiment, the organic solvent includes at least two of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, dimethyl ether, tetrahydrofuran, methyl acetate, ethyl acetate, methyl propionate, and diethyl carbonate.
[0047] Alternatively, a single solvent may not be able to simultaneously meet the multiple requirements of an electrolyte. For example, ethylene carbonate (EC) has a high dielectric constant and good film-forming properties, but its high viscosity leads to low ion mobility; dimethyl carbonate (DMC) has low viscosity and good flowability, but its dielectric constant is low. Therefore, mixing solvents can balance the advantages of both, improving conductivity and stability. At the same time, mixing different solvents can extend the operating temperature range of the electrolyte. For example, DMC performs better at low temperatures, while diethyl carbonate (DEC) can improve high-temperature performance; mixing them can handle both high and low temperature scenarios. Furthermore, mixing solvents can reduce the flammability risk of a single solvent and lower costs. For example, DMC has a high flash point and is non-flammable; mixing it with the flammable EC improves overall safety.
[0048] Optionally, the ratio of various organic solvents in the gel electrolyte satisfies 1:1.
[0049] Alternatively, organic solvents are used as carriers for lithium salts to ensure that the lithium salts can dissolve and maintain sufficient ionic conductivity. They typically have high dielectric constants to promote the dissociation of lithium salts and need to have a wide operating temperature range to function effectively under both low and high temperature conditions.
[0050] In one feasible embodiment, the film-forming aid includes at least one of: vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, propylene sulfite, vinyl sulfate, trimethylsilyl borate, trimethylsiloxypropanesulfonate, and cyclohexylbenzene.
[0051] Optionally, film-forming aids are primarily used to help form a stable SEI film, which is crucial for improving battery cycle efficiency and safety. These aids can preferentially reduce during the first charge of the battery, generating a uniform, dense, electronically insulating but ion-permeable film to prevent further electrolyte decomposition.
[0052] Optionally, if multiple film-forming aids are added to the gel electrolyte, the ratio between the various film-forming aids shall satisfy 1:1.
[0053] In one feasible embodiment, the solid electrolyte includes: LLTO, LATP, LLZO, Li₂S-P₂S₅, Li 10 GeP2S 12 At least one of Li3YCl6 and Li3YBr6.
[0054] Optionally, introducing solid electrolyte components into the gel electrolyte can enhance mechanical strength and safety while reducing the risk of liquid electrolyte leakage. Solid electrolytes can also improve interfacial stability and inhibit lithium dendrite growth, thereby improving battery safety and cycle life, thus forming a gel electrolyte system that combines the high ionic conductivity of liquid electrolytes with the safety of solid electrolytes.
[0055] Optionally, vinylene carbonate (VC) can undergo free radical polymerization on the surface of the carbon anode to generate polyalkyl lithium carbonate, thereby effectively inhibiting the co-insertion reaction of solvent molecules, while having no side effects on the cathode.
[0056] Alternatively, fluoroethylene carbonate (FEC) can inhibit electrolyte decomposition and form a tightly structured and better-performing SEI film on the negative electrode, thereby reducing battery impedance and improving the low-temperature performance of the electrolyte.
[0057] Alternatively, the high reactivity of vinyl ethylene carbonate (VEC) allows it to effectively participate in the SEI film formation process at lower concentrations, which helps improve the overall performance of the battery.
[0058] Alternatively, propylene sulfite (PS), due to its unique chemical structure, may help form a more uniform and dense protective layer, thereby reducing the occurrence of side reactions.
[0059] Alternatively, trimethylsilyl borate (TMSB) can react with lithium salts to form lithium borate compounds, which help to construct more stable SEI films.
[0060] Alternatively, trimethylsiloxypropanesulfonate (TMSP) can improve the stability of the electrode / electrolyte interface, especially under high temperature conditions, and help prevent gas generation and reduce the risk of battery swelling.
[0061] Alternatively, cyclohexylbenzene (CHB) forms a passivation layer on the electrode surface by undergoing oxidative polymerization under overcharge conditions to prevent further electrochemical reactions and can also play a certain role in preventing gas expansion, helping to maintain the internal pressure balance of the battery.
[0062] In one feasible embodiment, the gel electrolyte comprises, by mass percentage: 0.1-1% polymer matrix, 0.1-1% initiator, 10-20% lithium salt, 20-65% organic solvent, 0.5-25% film-forming aid and 0.1-1% solid electrolyte, wherein the polymer matrix includes a polymer matrix and a polymer sub-matrix.
[0063] Optionally, by mass percentage, the gel electrolyte comprises: 0.1-1% polymer matrix, 0.1-1% initiator, 10-20% lithium salt, 20-65% organic solvent, 0.5-25% film-forming aid, and 0.1-1% solid electrolyte, wherein the polymer matrix comprises a polymer main matrix and a polymer sub-matrix, and the mass ratio between the polymer main matrix and the polymer sub-matrix satisfies 1:(0.1-0.5).
[0064] Optionally, the mass ratio between the polymer matrix and the polymer sub-matrix satisfies 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, etc.
[0065] Optionally, if the polymer matrix content is too high, it will lead to an increase in system viscosity, making processing more difficult and potentially causing a decrease in conductivity. Conversely, if the polymer matrix content is insufficient, it cannot provide enough mechanical support, which may lead to an unstable gel structure that is prone to cracking or dissolving in the electrolyte, thereby affecting the safety and stability of the battery. Therefore, in the embodiments of this application, the polymer matrix content in the gel electrolyte is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0066] Optionally, excessive initiator may lead to an excessively rapid reaction rate, causing localized overheating or even explosive polymerization, which not only affects the quality of the product but may also pose safety hazards. Insufficient initiator dosage may result in incomplete polymerization, leading to a less dense gel network and affecting the overall performance and stability of the gel electrolyte. Therefore, in the embodiments of this application, the initiator content in the gel electrolyte is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0067] Optionally, excessively high salt concentrations can significantly increase the viscosity of the solution, reduce ion conduction efficiency, and increase costs. Furthermore, excessively high lithium salt concentrations may lead to unnecessary side reactions with the electrode materials, impairing battery life. Insufficient lithium salt concentrations, on the other hand, cannot provide enough charge carriers, resulting in low ionic conductivity and consequently affecting battery efficiency. Therefore, in the embodiments of this application, the lithium salt content in the gel electrolyte is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.
[0068] Optionally, excessive organic solvents can dilute the system too much, weakening the role of the polymer matrix and reducing the mechanical strength and thermal stability of the gel electrolyte. Insufficient solvents, on the other hand, make it difficult to form a uniform gel network, potentially leading to excessively dry local areas that are detrimental to ion transport. Therefore, in the embodiments of this application, the content of organic solvents in the gel electrolytes is 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, and 65%.
[0069] Optionally, excessive film-forming aids may alter the surface properties of the membrane, such as reducing its hardness and affecting its durability; it may also affect compatibility with other components. Insufficient aids may make it difficult to achieve the desired film-forming effect, affecting the quality of the membrane and its protective function for the electrodes. Therefore, in the embodiments of this application, the content of film-forming aids in the gel electrolyte is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 5%, 10%, 15%, 20%, 25%, etc.
[0070] Optionally, an excessively high proportion of solid electrolyte may interfere with the ion conduction pathways within the gel electrolyte, leading to a decrease in conductivity. Insufficient solid electrolyte, on the other hand, will fail to effectively enhance the mechanical strength of the electrolyte and suppress dendrite growth. Therefore, in the embodiments of this application, the content of solid electrolyte in the gel electrolyte is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0071] In this embodiment, a three-dimensional network polymer, cross-linked by ester / amide bonds and possessing both the stability of fluoropolymers and the rigidity of PAN, is formed in the gel electrolyte. Esterification / amidation transforms the linear polymer into a network structure, improving the material's thermal stability and mechanical strength. The gel electrolyte combines solvent conduction, polymer network structure, and the lattice diffusion mechanism of solid electrolytes. Compared with traditional liquid electrolytes, this gel electrolyte significantly improves the safety performance of lithium-ion batteries, effectively solving the problems of easy leakage and flammability of liquid electrolytes. Simultaneously, through optimized component ratios and preparation processes, this gel electrolyte also improves the battery's energy density and rate performance, making it particularly suitable for high-rate applications such as drones. Furthermore, the synergistic effect of the three-dimensional network polymer structure and multiple ion conduction mechanisms formed in the gel electrolyte further enhances the battery's cycle stability and lifespan, providing a new technical solution for the application of lithium-ion batteries in fields with high safety requirements.
[0072] Furthermore, embodiments of this application also provide a method for preparing a lithium-ion battery, referring to... Figure 1 The preparation method of lithium-ion batteries includes the following steps:
[0073] Step S10: Provide an unfilled battery and a gel electrolyte;
[0074] In one feasible embodiment, positive and negative electrode sheets are provided, and the positive and negative electrode sheets are combined with a separator using a winding method or a Z-shaped stacking method. The wound or stacked battery cells are then installed into a battery case, wherein the battery case is a pouch, square, or cylindrical shape. Metal strips are then welded to both ends of the battery cell as current lead terminals, the battery is initially sealed, leaving an electrolyte injection port, and then the entire battery is dried to obtain an unfilled battery. A polymer matrix, initiator, lithium salt, organic solvent, solid electrolyte, and film-forming aid are mixed to obtain a gel electrolyte, wherein the polymer matrix includes: poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate.
[0075] Optionally, the positive electrode material can be lithium nickel cobalt manganese oxide (NCM811), the negative electrode material can be graphite, and the separator can be a three-layer composite separator of polypropylene / polyethylene / polypropylene (PP / PE / PP) with a porosity of 60% and a thickness of 20µm. The positive electrode sheet, separator, and negative electrode sheet are stacked in sequence and wound into a core, and the core is placed in a flexible aluminum-plastic film with a pre-reserved liquid injection port.
[0076] Optionally, the gel electrolyte comprises, by mass percentage: 0.1-1% polymer matrix, 0.1-1% initiator, 10-20% lithium salt, 20-65% organic solvent, 0.5-25% film-forming aid, and 0.1-1% solid electrolyte.
[0077] Optionally, the gel electrolyte further includes a polymer sub-matrix, which includes polyacrylonitrile and / or polyvinylidene fluoride-hexafluoropropylene.
[0078] Optionally, the initiator includes at least one of: di(2-ethylhexyl) dicarbonate, benzoyl peroxide, and potassium persulfate.
[0079] Optionally, the lithium salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBOB, LiDFOB, and LiPO2F2. Optionally, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, dimethyl ether, tetrahydrofuran, methyl acetate, ethyl acetate, methyl propionate, and diethyl carbonate.
[0080] Optionally, the solid electrolyte includes at least one of LLTO, LATP, LLZO, Li2S-P2S5, Li10GeP2S12, Li3YCl6, and Li3YBr6.
[0081] Optionally, the film-forming aid includes at least one of: vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, propylene sulfite, vinyl sulfate, trimethylsilyl borate, trimethylsiloxypropanesulfonate, and cyclohexylbenzene.
[0082] Optionally, the gel electrolyte of this embodiment exhibits a fluid state at room temperature, facilitating injection into the battery. After hot-pressing and curing, it forms a semi-solid gel with a three-dimensional network structure, effectively preventing electrolyte leakage and improving battery safety. This gel electrolyte forms a three-dimensional network polymer cross-linked by ester / amide bonds, possessing both the stability of fluoropolymers and the rigidity of PAN. Esterification / amidation transforms the linear polymer into a network structure, enhancing the material's thermal stability and mechanical strength. In this gel electrolyte, the PVFH matrix (PVDF-HFP) provides chemical stability and mechanical support, and the strong electronegativity of its fluorinated segments (-CF2-) may polarize adjacent MAH carbonyl groups, enhancing anhydride reactivity. This gel electrolyte combines solvent conduction, polymer network structure, and the lattice diffusion mechanism of solid electrolytes to form a multi-channel lithium-ion transport network, significantly improving the electrolyte's ionic conductivity. Using this gel electrolyte in batteries can produce lithium-ion batteries with high safety, high energy density, and excellent rate performance.
[0083] Step S20: Inject the gel electrolyte into the unfilled battery and let it stand for 16-48 hours to obtain a pre-charged battery;
[0084] In one feasible embodiment, a liquid injection machine is used in a low-humidity drying workshop to inject the gel electrolyte into the unfilled battery, and the battery is left to stand at room temperature for 16 to 48 hours to allow the gel electrolyte to fully wet the electrodes and separator, thus obtaining a pre-charged battery.
[0085] Optionally, in a dry workshop with a dew point temperature below -40°C, the above-mentioned gel electrolyte is injected into the battery using a precision liquid injection machine, with an injection volume of 3 to 4.5g, for example, 3.5g.
[0086] Step S30: Precharge the pre-charged battery and heat-press it to obtain a lithium-ion battery.
[0087] In one feasible embodiment, the pre-charged battery is pre-charged by a pressure formation cabinet, which enables the battery electrode to form a stable SEI film and allows the gel electrolyte to better shuttle through the electrode. Then, it is hot-pressed and cured under the conditions of temperature 45-75°C and pressure 0.6-1 MPa. During this process, the initiator decomposes at high temperature to generate free radicals, which trigger the cross-linking reaction of the polymer matrix to form a three-dimensional network structure. The electrolyte changes from liquid to gel state and is then formed into a lithium-ion battery through degassing, encapsulation, cutting, and folding.
[0088] Optionally, the hot pressing temperature is 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, etc. The hot pressing pressure is 0.6Mpa, 0.7Mpa, 0.8Mpa, 0.9Mpa, 1Mpa, etc.
[0089] Optionally, the hot-press curing time is 4 to 10 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc.
[0090] In this embodiment, pre-charging activates the internal chemical reaction of the battery at a lower current, resulting in a more moderate temperature rise inside the battery. This reduces heat accumulation and potential thermal runaway risks caused by rapid charging or discharging. Pre-charging also helps form a stable solid electrolyte interphase (SEI) layer, effectively preventing adverse reactions between the electrolyte and electrode materials and enhancing battery safety. Furthermore, this embodiment uses poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate (PVFH-PVCA) as the main polymer matrix and combines it with a polymer sub-matrix. Crosslinking is achieved by generating free radicals through an initiator, forming a three-dimensional network structure. This three-dimensional network structure restricts the mobility of polymer chains, enhancing the mechanical strength and toughness of the electrolyte, making it more resistant to external pressure and internal stress, reducing microcracks and delamination that may occur during battery cycling, and improving stability. Simultaneously, it provides a continuous path for ion transport, effectively maintaining the high ionic conductivity of the electrolyte. Furthermore, PVFH-PVCA itself has good chemical inertness, and the presence of fluorine in particular endows the material with excellent antioxidant and corrosion resistance. Therefore, these properties are further enhanced after crosslinking, which helps to prevent the decomposition of the electrolyte under high pressure conditions and further improves the stability of the gel electrolyte.
[0091] In order to enable those skilled in the art to clearly understand the details and operations of the above embodiments of this application, and to demonstrate the significant improvement in performance of the embodiments of this application, the above technical solutions are illustrated below through multiple embodiments.
[0092] Example 1
[0093] (1) Provide a gel electrolyte, which, by weight percentage, comprises: 0.5% PVFH-PVCA, 0.5% EHP, 15% LiPF6, 30% ethylene carbonate, 30% dimethyl carbonate, 23.7% vinylene carbonate and 0.3% LLTO;
[0094] (2) Provide an unfilled battery, wherein the positive electrode material is selected from lithium nickel cobalt manganese oxide (NCM811), the negative electrode material is selected from graphite, and the separator is selected from a three-layer composite separator of polypropylene / polyethylene / polypropylene (PP / PE / PP) with a porosity of 60% and a thickness of 20um.
[0095] (3) Inject the gel electrolyte into the unfilled battery, the injection volume is 3.5g, let it stand for 24h to obtain the pre-charged battery;
[0096] (4) The pre-charged battery is pre-charged with a charging current of 0.1C, a charging voltage of 4.2V, and a charging time of 10h. The battery is then hot-pressed and cured at 60℃ and 0.8MPa for 8h to obtain a lithium-ion battery.
[0097] Example 2
[0098] The experimental procedure was the same as in Example 1, except that the gel electrolyte, by mass percentage, included: 0.3% PVFH-PVCA, 0.8% KPS, 18% LiBOB, 30% propylene carbonate, 30% dimethyl ether, 20.5% vinyl ethylene carbonate, and 0.4% Li3YCl6.
[0099] Example 3
[0100] The experimental procedure was the same as in Example 1, except that the gel electrolyte, by mass percentage, included: 1% PVFH-PVCA, 1% BPO, 20% LiBOB, 20% ethylene carbonate, 20% tetrahydrofuran, 20% ethyl acetate, 17.5% trimethylsilyl borate and 0.5% Li2S-P2S5.
[0101] Example 4
[0102] The experimental procedure was the same as in Example 1, except that, by mass percentage, the gel electrolyte included: 0.5% PVFH-PVCA, 0.5% PAN, 0.5% KPS, 0.5% EHP, 10% LiFSI, 10% LiPF6, 20% ethylene carbonate, 20% dimethyl carbonate, 20% ethyl methyl carbonate, 8.75% vinylene carbonate, 8.75% fluoroethylene carbonate, 0.2% LLZO, and 0.3% Li3YBr6.
[0103] Comparative Example 1
[0104] The experimental procedure was the same as in Example 1, except that, by mass percentage, the gel electrolyte comprised: 0.8% PAN, 0.3% BPO, 15% LiFSI, 30% ethylene carbonate, 30% methyl ethyl carbonate, 23.7% fluoroethylene carbonate, and 0.2% Li 10 GeP2S 12 .
[0105] Comparative Example 2
[0106] The experimental procedure was the same as in Example 1, except that the gel electrolyte, by mass percentage, included: 0.1% PAN, 0.1% EHP, 18% LiPF6, 30% ethylene carbonate, 30% diethyl carbonate, 21.7% propylene sulfite, and 0.1% LATP.
[0107] The performance of the lithium-ion batteries of Examples 1 to 4 and Comparative Examples 1 and 2 was tested, and the experimental results are shown in Table 1 below.
[0108] Table 1:
[0109]
[0110] Based on the above experimental results, it can be seen that the short-term cycle stability of the batteries prepared in Examples 1-4 of this application is similar to that of Comparative Examples 1-2, while the long-term cycle stability is better and the cycle expansion rate is lower.
[0111] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the patent protection scope of this application.
Claims
1. A gel electrolyte, characterized in that, The gel electrolyte comprises: a polymer matrix, an initiator, a lithium salt, an organic solvent, a solid electrolyte, and a film-forming aid, wherein the polymer matrix comprises: poly(vinylidene fluoride-hexafluoropropylene)-polyacrylonitrile-maleic anhydride-ethylene carbonate.
2. The gel electrolyte as described in claim 1, characterized in that, The gel electrolyte comprises, by weight percentage: 0.1-1% polymer matrix, 0.1-1% initiator, 10-20% lithium salt, 20-65% organic solvent, 0.5-25% film-forming aid, and 0.1-1% solid electrolyte.
3. The gel electrolyte as described in claim 1, characterized in that, The gel electrolyte also includes a polymer sub-matrix, which includes polyacrylonitrile and / or polyvinylidene fluoride-hexafluoropropylene.
4. The gel electrolyte as described in claim 1 or 2, characterized in that, The initiator includes at least one of di(2-ethylhexyl) dicarbonate, benzoyl peroxide, and potassium persulfate.
5. The gel electrolyte as described in claim 1 or 2, characterized in that, The lithium salt includes at least one of LiPF6, LiFSI, LiTFSI, LiBOB, LiDFOB, and LiPO2F2.
6. The gel electrolyte as described in claim 1 or 2, characterized in that, The organic solvent includes at least two of the following: ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, dimethyl ether, tetrahydrofuran, methyl acetate, ethyl acetate, methyl propionate, and diethyl carbonate.
7. The gel electrolyte as described in claim 1 or 2, characterized in that, The solid electrolytes include: LLTO, LATP, LLZO, Li₂S-P₂S₅, and Li. 10 GeP2S 12 At least one of Li3YCl6 and Li3YBr6.
8. The gel electrolyte as described in claim 1 or 2, characterized in that, The film-forming aid includes at least one of the following: vinylene carbonate, fluoroethylene carbonate, vinyl ethylene carbonate, propylene sulfite, vinyl sulfate, trimethylsilyl borate, trimethylsiloxypropanesulfonate, and cyclohexylbenzene.
9. A method for preparing a lithium-ion battery, characterized in that, The method includes the following steps: Provided unfilled battery and gel electrolyte, wherein the gel electrolyte is the gel electrolyte as described in any one of claims 1 to 8; The gel electrolyte is injected into the unfilled battery and left to stand for 16–48 hours to obtain a precharged battery. The pre-charged battery is pre-charged and then hot-pressed to solidify, thus obtaining a lithium-ion battery.
10. A lithium-ion battery, characterized in that, The lithium-ion battery comprises a gel electrolyte as described in any one of claims 1 to 8, or is prepared by the method described in claim 9.
Citation Information
Cited By
Solid electrolyte diaphragm, preparation method and lithium battery
CN121584150A